2017
DOI: 10.19044/esj.2017.v13n17p206
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Des Indices Pluviométriques Extrêmes Par L'analyse De Modèles Climatiques Régionaux Du Programme CORDEX: Les Projections Climatiques Sur Le Sénégal

Abstract: This study aims at characterizing the extreme rainfall events over West Africa particularly in the Sahel region and Senegal by 2100 (far future) under the greenhouse gas emission scenario RCP8.5 by analyzing the simulations of four (4) regional climate models (RCMs) of CORDEX (Regional COordinated climate Downscaling Experiment) program. The study of these extreme climate indices is crucial for the understanding of the impacts of climate change on some vital socio-economic sectors such as the agriculture in Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 7 publications
5
13
0
Order By: Relevance
“…The second series of simulations (climate projections, period 2006-2100) aims to analyze the future evolution of the climate. In this context, several studies have been carried out (Sarr and Camara, 2017;Diallo et al, 2016;Sylla et al, 2016;Mariotti et al, 2014;Giorgi et al, 2014;Laprise et al, 2013) to identify the future evolution of the precipitation and the mean surface temperature. However, few research works have been devoted in studying the future evolution of extreme temperature events and its impact on human health in West Africa and particularly in Senegal.…”
Section: Introductionmentioning
confidence: 99%
“…The second series of simulations (climate projections, period 2006-2100) aims to analyze the future evolution of the climate. In this context, several studies have been carried out (Sarr and Camara, 2017;Diallo et al, 2016;Sylla et al, 2016;Mariotti et al, 2014;Giorgi et al, 2014;Laprise et al, 2013) to identify the future evolution of the precipitation and the mean surface temperature. However, few research works have been devoted in studying the future evolution of extreme temperature events and its impact on human health in West Africa and particularly in Senegal.…”
Section: Introductionmentioning
confidence: 99%
“…The drawback of the above procedure of bias correction is the assumption of constant bias between the reference and future periods . However, we will accept this assumption as most of the recent studies did (Sarr and Camara, 2017) as mentioned earlier, bias correction and spatial disaggregation relies on finer-scale observation data and consists of the following steps: (1) aggregate finer-scale observed data to a RCM-specific scale; (2) correct the RCM's systematic biases through quantile mapping; and (3) disaggregate biascorrected outputs to a finer scale (Batablinlè et al, 2018). An equiratio cumulative distribution function matching (equiratio CDFm): The statistical transformation can be written as:…”
Section: Methodsmentioning
confidence: 89%
“…Pluviometric regimes will also be affected and may decrease of more than 20 % to 30 % compared to the reference (Bigot, 2003). Other studies indicated an increase in extreme rainfall events, particularly in Sahel (Nicholson and Webster, 2007) but also a decrease in Nigeria (Oguntundé et al, 2011) and (Easterling et al, 2000), Guinea Conakry (Aguilar et al, 2009), in eastern Niger (Ozer et al, 2009), in Ivory-Coast (Soro et al, 2014), in Benin (Yèkambèssoun et al, 2017) and in South Africa (Mason et al, 1999). In the northern part of Africa, there is a tendency towards wetter conditions; in contrast with the eastern part, experienced with more drying trends, although, these trends are of low significance.…”
Section: Introductionmentioning
confidence: 96%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License Sarr and Camara, 2017). Agriculture plays a significant role in the livelihood and economy growth of most African people (Kotir, 2010).…”
Section: Introductionmentioning
confidence: 91%